Culture, Racial Socialization, and Positive African American Youth Development. (August 2016) - Grills, Cheryl; Cooke, Deanna; Douglas, Jason; Subica, Andrew; Villanueva, Sandra; Hudson, Brittani
Positive youth development is critical for African American youth as they negotiate a social, political, and historical landscape grounded in systemic inequities and racism. One possible, yet understudied, approach to promote positive youth development is to increase African American youth consciousness and connection to their Africentric values and culture. The primary purpose of this article was to investigate the degree to which cultural and group consciousness factors (i.e., cultural orientation, Africentric values, and racial socialization) predicted positive youth development (i.e., future orientation, prosocial behavior, political/community, and social justice/equality civic mindedness) and how these might differ by gender. This article utilized survey data from 1, 930 African American youth participants of the Pen or Pencil™ mentoring program. Results generally indicated that cultural orientation, Africentric values and, to a lesser degree, racial socialization, predicted positive youth development variables, with these effects varying by gender. These findings suggest that enhancing cultural consciousness may support the positive development of African American youth, although male and female youth may respond to these efforts in different ways.